MEMBANDINGKAN BIAYA DINDING BATA RINGAN DAN BATA MERAH BANTUAN RUMAH TIDAK LAYAK HUNI - Heru Suseno (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2022)
ABSTRACT Uninhabitable houses are houses that do not meet building safety requirements, minimum adequacy of building area and occupant health. Uninhabitable houses need walls that can protect from heat, cold air, rain, dust, noise, wild animals and others. The wall is part of the building as a barrier from one room to another. The wall serves to limit the outer space with the inner space as. There are two options available, namely red brick and hebel or light brick. Red brick comes from clay that is molded, then burned. Lightweight or hebel bricks are made in the factory using machines. We can choose whether the wall is using red brick or hebel. Calculation of wall work complete with plastering and plastering based on the Analysis of the Work Unit Price (AHSP) for the City of Semarang 2022 with an area of 483.84 m², the difference in the cost of work for each wall building material is obtained. The red brick has a cheaper work cost of Rp. 195,139,740.60, while the cost of light brick wall work is more expensive at Rp. 223,275,036.60. So that the difference in the price of Rp. 28,135,296.00. Keywords : Uninhabitable House Walls, Red Brick and Light Brick, Cost Difference